Repeated Bout Effect of Downhill Running on Physiological Markers of Effort and Post Exercise Perception of Soreness in Trained Female Distance Runners - Jason Tallis; Caitlin McMorrow; Sharn P. Shelley; Steven J. Eustace (MDPI AG, 2024)
This study examined the effect of repeated bouts of level and downhill running on physiological markers of effort and exercise-induced muscle soreness in trained female distance runners. Ten participants (Age: 24.4 ± 2.0 years; V̇O2peak: 52.9 ± 1.1 mL·kg−1·min−1), naïve to downhill running, completed six alternate 5 min trials of level and downhill running (−15%) at a 70% velocity at V̇O2peak on two occasions, three weeks apart. Perceived muscle soreness was measured upon completion and in the 72 h post exercise. V̇O2, Heart Rate (HR), Blood Lactate (BLa), and Respiratory Exchange Ratio (RER) were lower running downhill (p < 0.016, ηp2 > 0.541). For the first downhill run, Rating of Perceived Exertion (RPE) was higher compared to that for level running (p = 0.051; d = 0.447), but for the remaining trials, RPE was lower when running downhill (p < 0.004; d > 0.745). V̇O2, HR, and RER were not different in the second bout (p > 0.070, ηp2 < 0.318); however, V̇O2 was lower in each downhill trial (Δ = 1.6-2.2 mL·kg−1·min−1; d = 0.382-0.426). In the second bout, BLa was lower (p = 0.005, ηp2 = 0.602), RPE in the first trial was lower (p = 0.002; d = 0.923), and post exercise perceived soreness of the gastrocnemius, quadriceps, and hamstrings was attenuated (p < 0.002; ηp2 > 0.693). Perceived soreness of the gluteal muscles was lower in the second bout immediately post exercise, 24 h, and 48 h post exercise (p < 0.025; d > 0.922). A repeated bout of downhill running attenuated perceived muscle soreness and may modulate the physiological and perceived physical demand of a second bout of level and downhill running.